Cooling forests, calmer hearts: Urban forest structure, microclimate and heat relief in adolescents - Sophie Feiertag; Daniel A. Scheller; Jan Schmid-Ellinger; Anna-Katharina Eisen; Filip Mess; Annette Menzel (Urban Forestry & Urban Greening, 2026)

Mobilized-clay-driven toppling: A new mechanism resolving the “energy paradox” of under-dip slope failure in flysch terrains - Thanh-Tùng Nguyễn; Ivo Baroň; Filip Hartvich; Jiří Havlík; Lenka Kociánová; Jan Klimeš; Jan Černý; Martin Šutjak; Václav Dušek; Cheng-Han Lin; Chia-Han Tseng; Yi-Chin Chen; et al. (Landslides, 2026)

Enterococcal bacteremia in children with malignancy or after hematopoietic stem cell transplantation: real-world multicenter data from a nationwide survey in Poland (2014–2021) - Tomasz Ociepa; Aleksandra Królak; Hubert Kluk; Krzysztof Czyżewski; Kamila Jaremek; Oliwia Grochowska; Patrycja Zalas-Więcek; Katarzyna Derwich; Jacek Wachowiak; Agnieszka Mizia-Malarz; Weronika Stolpa; Karolina Baranowska; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Probiotic-Containing Nanofiber-Based Dental Floss Suppresses Subgingival Red Complex Periopathogens: A Randomized Double-Blind Crossover Trial - Filip Hromcik; Pavla Holochova; Jan Bohm; Eva Kuzelova Kostakova; Zdenek Pokorny; Filip Ruzicka; Petra Borilova Linhartova (Probiotics and Antimicrobial Proteins, 2026)
Recently, a dental nanofloss containing a probiotic ( Ligilactobacillus salivarius ; LS -nanofloss) was developed by our team. This study aimed to evaluate: (i) its impact on subgingival plaque accumulation and gingival bleeding, and (ii) retention of selected subgingival periopathogens and the introduced probiotic bacteria, and (iii) its effect on the quantity of red complex periopathogens in the subgingival environment. This randomized, double-blind, crossover trial was conducted in 30 healthy male participants. Each subject underwent professional flossing and subsequently used LS -nanofloss/probiotic-free (control) nanofloss at two separate 14-day periods, always followed by a 14-day wash-out. Clinical assessments (subgingival plaque accumulation and gingival bleeding) were performed at five time points; subgingival plaque samples were collected at seven time points for quantitative analysis of total bacterial DNA, L. salivarius , a cariogenic bacterium Streptococcus mutans , and red complex periopathogens. Both nanofloss types significantly reduced plaque accumulation and gingival bleeding after 14 days ( p < 0.05), especially in the anterior regions; these improvements, however, regressed after the wash-out period. L. salivarius DNA was detected in 93.3% of samples after professional flossing, 36.7% after self-flossing, and 13.3% even after the wash-out period. The use of LS -nanofloss was associated with a significant reduction in red complex periopathogens ( p < 0.05). The investigated L. salivarius -containing nanofloss proved to be an effective oral hygiene device for subgingival introduction of this probiotic strain. Its application reduced the relative quantity of red complex periopathogens in the subgingival environment, showing potential to prevent the development of periodontitis. The trial was registered retrospectively on 2/9/2025 as NCT07149493.

National Surveillance of Candidemia in the Czech Republic: Preliminary Results from the 2023 Multicentre Study - Pavlína Lysková; Radim Dobiáš; Matěj Bezdíček; Vít Hubka; Petra Sumerauerová; Daniela Lžičařová; Iva Kocmanová; Vladimír Buchta; Ivana Prošková; Helena Janouškovcová; Petra Olišarová; Kateřina Svobodová; et al. (Mycopathologia, 2026)

Delayed plant genetic responses to forest edge dynamics and their conservation implications - Lore Hostens; Christophe Metsu; Elissar Alam; Kasper Van Acker; Gerrit Peeters; Sander de Beer; Yannick Gansemans; Eugenija Kupcinskiene; Lina Jociene; Edvina Krokaite‐Kudakiene; Jolina Paulssen; Leonie Mazalla; et al. (Conservation Biology, 2026)
Understanding genetic responses to forest dynamics is essential for predicting the long‐term viability of understory plant populations and for developing effective conservation strategies. We investigated genetic extinction debt and colonization credit in broad‐leaved enchanter's nightshade ( Circaea lutetiana ), a clonal forest understory species, across its European range. Using pooled genotype‐by‐sequencing data from 40 forest edge and core populations, we examined to what extent population size, latitude, and historical changes in forest configuration may predict genetic diversity. Historical forest configuration profoundly shaped present‐day genetic diversity. Long‐established forest edge populations exhibited significantly reduced allelic richness (−9%) compared with core populations, indicating the partial payoff of a genetic extinction debt. In contrast, populations from recently established forest edges maintained allelic richness similar to core populations, suggesting delayed population genetic responses to land‐use changes. Finally, populations established in areas that were afforested during the past 250 years exhibited lower allelic richness (−10%) than historical forest core populations, indicating a delay in genetic recovery and thus a potential genetic colonization credit. Our results highlight that C. lutetiana populations are not at equilibrium with the current forest configuration, underscoring the role of lagged genetic responses across very long periods. Population size, and to a lesser extent connectivity, further mediated genetic diversity, with smaller, isolated populations being particularly vulnerable to genetic erosion. Given the limited research on delayed evolution in forest understory species, our results improve understanding of extinction risk dynamics and underscore the need for history‐informed restoration efforts.

Evaporite minerals from the coal mines of the Czech part of the Upper Silesian Basin, including a new mineral králíkite (BaCl2·2H2O) - Dalibor Matýsek; Jakub Jirásek; Juraj Majzlan; Jan Filip; Michal Osovský; Jörg Göttlicher (International Journal of Coal Geology, 2026)

Paleo-landslide analysis reveals underestimated seismic hazards in the outer Western Carpathians - Thanh-Tùng Nguyễn; Ivo Baroň; Rostislav Melichar; Jia-Cian Gao; Filip Hartvich; Cheng-Han Lin; Jan Klimeš; Martin Šutjak; Lenka Kociánová; Václav Dušek; František Bárta; Chia-Han Tseng; et al. (Engineering Geology, 2026)

Temporal trends in porcine and bovine semen characteristics: A retrospective long-term analysis of semen production data - Britta Hensel; Sophie Henneberg; Filip Schröter; Maren Hürland; Jan-Hendrik Osmers; Stefan Geissendörfer; Matthias Lautner; Markus Jung; Martin Schulze (Animal Reproduction Science, 2026)

Contactless laser positioning system for tracking three-dimensional kinematic behaviour of rock slope fractures and active faults tested on a large rockslide in the Western Alps - Ivo Baroň; Tomáš Trčka; Jaroslav Čejka; Pavel Škarvada; Daniel Dolejška; Riccardo Vassallo; Laurent Metral; Matt Rowberry; Jan Balek; Filip Hartvich (Landslides, 2026)

Dual-organoid biosensor for monitoring cardiac conduction disturbances in vitro - Filip Svěrák; Daniil Kabanov; Šimon Vrana; Deborah Beckerová; Jan Máchal; Martin Pešl; Vladimír Rotrekl; Jan Přibyl (Analytica Chimica Acta, 2026)

Life and death in the medieval mining centre of Kutná Hora - reconstructing diets during the recurrent mortality crises of the 14th century AD (Czechia) - Sylva Drtikolová Kaupová; Jan Frolík; Petr Velemínský; Filip Velímský; Zdeněk Vytlačil; Hana Brzobohatá (Archaeological and Anthropological Sciences, 2026)
During the 14th century, the inhabitants of Kutná Hora, an important urban centre in the Kingdom of Bohemia, were exposed to recurrent mortality crises. Using stable carbon and nitrogen isotopes, this study investigates the relationship between diet and the famine of 1318 and the plague outbreaks after 1346. Together with a comparative sample from regular graves, a total of 112 bone samples were collected, supplemented by 70 first permanent molars subjected to the dentine serial sampling method. The mean bone carbon isotope value ( δ 13 C) was − 19.3 ± 0.3‰. The mean bone nitrogen isotope value ( δ 15 N) was 12.0 ± 0.7‰. Individuals from famine graves showed lower δ 15 N values than those from regular graves. Individuals who survived into adulthood (survivors) showed higher δ 15 N values than those who died before adulthood i.e. non-survivors (even in the reduced sample of regular graves). Weaning age as estimated by WEAN software was 2.8 years. There was a significant difference between survivors and non-survivors but due to the smaller sample size, the confounding effect of other factors cannot be excluded. The population sample studied had a diet based on C3 plants, with a significant contribution from animal products and/or fish. Lower δ 15 N values in famine victims suggested that lower intake of animal products increased the likelihood of starvation. Plague mortality does not appear to be related to dietary patterns. Apart from catastrophic events, current data suggest that a low proportion of animal products in the diet and perhaps earlier weaning reduced the chances of survival to adulthood.

Synergistic pharmaceutical interactions with nanoscale iron nitrides and natural organic matter - Veronika Veselská; Josef Kašlík; Diego Baragaño; Anaëlle Simonneau; Thomas Thiebault; Martin Petr; Jan Filip; Jean-Sébastien Moquet; Gildas Ratié (Chemical Engineering Journal, 2025)

Minor Amaryllidaceae alkaloids as inspiration for development of highly selective butyrylcholinesterase inhibitors: design, synthesis, and biological evaluation - Lucie Cahlíková; Filip Pidaný; Jan Korábečný; Daniela Suchánková; Jana Křoustková (Phytochemistry Letters, 2025)

Did Forefather Czech know he was standing on a fossil lava lake? Revisiting the Oligocene Říp Hill volcano, Bohemian Massif - Filip Tomek; Jan Černý; Michal Lutovský; Lubomil Pospíšil; Petr Vitouš; Luboš Sokol; Ema Danielová; Zuzana Hájková (International Geology Review, 2025)

Reactivity measurement using pulsed neutron source methods on VR-1 and VR-2 reactors and their verification by SERPENT code - Michal Herčík; Jan Rataj; Ondřej Huml; Filip Fejt (Annals of Nuclear Energy, 2025)

Impact of pollution on the temperature sensitivity of multiple Norway spruce tree-ring parameters in Central Europe - Yumei Jiang; Krešimir Begović; Martin Lexa; Juliana Nogueira; Georg von Arx; Jan Tumajer; Ryszard Kaczka; Filip Oulehle; Nataliya Korolyova; Jesper Björklund; Kristina Seftigen; Vaclav Treml; et al. (Agricultural and Forest Meteorology, 2025)

Photoreforming of PET and PLA microplastics for sustainable hydrogen production using TiO2 and g-C3N4 photocatalysts - Petr Praus; Lenka Řeháčková; Miroslava Filip-Edelmanová; Anna Gavlová; Martin Koštejn; Radim Škuta; Jan Bednárek; Petr Bednář; Kamila Kočí (Journal of Environmental Chemical Engineering, 2025)

Thermo-Chemical recycling of polypropylene via high-power microwave plasma gasification: Syngas and metal carbide production - Jafar Fathi; Michal Hlína; Tomáš Mates; Maksym Buryi; Vineet Singh Sikarwar; Radek Mušálek; Shelja Sharma; Michal Lojka; Adéla Jiříčková; Ondřej Jankovský; Jan Riedl; Miroslav Karlík; et al. (Chemical Engineering Journal, 2025)

Complete historical chronology of complex landslide movements? Improving the tree-ring based results using multidisciplinary approaches - Karel Šilhán; Jan Balek; Jan Klimeš; Jan Blahůt; Filip Harvich; Pavel Raška; Jiří Riezner; Martin Šťastný (CATENA, 2025)

Impact of groundwater solutes on the fate and reactivity of nanoscale iron nitride particles - Jana Křížek Oborná; Miroslav Brumovský; Vesna Micić; Josef Kašlík; Jan Filip (Journal of Environmental Chemical Engineering, 2025)

A novel type of planar reference electrodes based on ionic liquids - Julia Kuczak; Justyna Wojcieszek; Marek Królikowski; Marta Królikowska; Jan Dominiczak; Jakub Krzemiński; Filip Budny; Izabela Wojciechowska; Adrian Kopytowski; Andrzej Pepłowski; Łukasz Górski (Analytica Chimica Acta, 2025)

Measurement of gamma field inside the biological concrete shielding of VVER-1000 Mock-Up at the LR-0 reactor - Tomáš Czakoj; Michal Košťál; Evžen Novák; Jan Šimon; Martin Schulc; Zdeněk Matěj; Filip Mravec; František Cvachovec; Tomáš Urban; Evžen Losa (Annals of Nuclear Energy, 2025)

Broomstick experiment with copper in VR-1 reactor - Michal Košťál; Evžen Losa; Tomáš Czakoj; Stanislav Simakov; Marek Zmeškal; Martin Schulc; Jan Šimon; Vojtěch Rypar; Evžen Novák; František Cvachovec; Filip Mravec; Václav Přenosil; et al. (Annals of Nuclear Energy, 2025)

Milk thistle (Silybum marianum L. Gaertner) oilseed cake flour functional, nutritional and antioxidant characteristics as effect of cultivar and preparation process - Veronika Bártová; Jan Bárta; Markéta Jarošová; Jan Bedrníček; František Lorenc; Adéla Stupková; Josef Švajner; Pavel Smetana; Jan Kyselka; Vladimír Filip; Zbyněk Zdráhal; Marie Bjelková (Food Bioscience, 2025)

Long-term movement activity and internal structure of deep-seated landslide by using dendrochronology analysis and electric resistivity tomography in flysch rocks, Carpathians, Czech Republic - Jan Klimeš; Filip Hartvich; Karel Šilhán (Landslides, 2024)

Comparative analysis of cyanobacterial communities in gypsum outcrops: insights from sites in Israel and Poland - Kateřina Němečková; Jan Mareš; Filip Košek; Adam Culka; Jan Dudák; Veronika Tymlová; Jan Žemlička; Jan Jehlička (Extremophiles, 2024)

Sulfidation of air-stable iron nanoparticles: A novel strategy how to boost their reactivity demonstrated on Cr(VI) reduction - Viktorie Víchová; Jana Křížek Oborná; Martin Petr; Jana Soukupová; Radka Pechancová; Tomáš Pluháček; Jan Filip (Journal of Water Process Engineering, 2024)

Unveiling trends in migration of iron-based nanoparticles in saturated porous media - Veronika Veselská; Leonardo Magherini; Carlo Bianco; Jan Šembera; Petr Parma; Viktorie Víchová; Rajandrea Sethi; Jan Filip (Journal of Environmental Management, 2024)

Mitochondrial damage precedes the changes of glutathione metabolism in CdCl2 treated neuronal SH-SY5Y cells - Pavlina Nyvltova; Jan Capek; Jiri Handl; Filip Petira; Erika Rousarova; Lenka Ticha; Stepanka Jelinkova; Tomas Rousar (Food and Chemical Toxicology, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Urbanisation-associated shifts in the avian metabolome within the annual cycle - Hannah Watson; Jan-Åke Nilsson; Einar Smith; Filip Ottosson; Olle Melander; Arne Hegemann; Utku Urhan; Caroline Isaksson (Science of The Total Environment, 2024)

Quarter century of mercury litterfall at a coniferous forest responding to climate change, Central Europe - Tomáš Navrátil; Jan Rohovec; Tereza Nováková; Michal Roll; Pavel Cudlín; Filip Oulehle (Environmental Science and Pollution Research, 2024)

Quantifying sediment sources, pathways, and controls on fluvial transport dynamics on James Ross Island, Antarctica - Christopher D. Stringer; John F. Boyle; Filip Hrbáček; Kamil Láska; Ondřej Nedělčev; Jan Kavan; Michaela Kňažková; Jonathan L. Carrivick; Duncan J. Quincey; Daniel Nývlt (Journal of Hydrology, 2024)

Measurement of prompt neutron capture gamma coming from iron and chlorine - Tomáš Czakoj; Michal Košťál; Evžen Novák; Evžen Losa; Jan Šimon; Martin Schulc; Filip Mravec; František Cvachovec; Jan Rataj; Zdeněk Matěj (Annals of Nuclear Energy, 2024)

Nitrates directive restriction: To change or not to change in terms of climate change, that is the question - Hana Středová; Petra Fukalová; Filip Chuchma; Jan Haberle; Tomáš Středa (Science of The Total Environment, 2024)

Prediction of the minimum ignition energy of dust clouds based on heat transfer and particle reaction kinetics - Tengfei Chen; Jo Van Caneghem; Jan Degrève; Jan Berghmans; Filip Verplaetsen; Maarten Vanierschot (Process Safety and Environmental Protection, 2024)

Corrigendum to “Source area morphometry and high depletion rate of landslides may indicate their coseismic origin” [Engineering Geology 330 (2024) 107424] - Ivo Baroň; Jan Jelének; Jan Klimeš; Jia-Jyun Dong; Rostislav Melichar; Martin Šutjak; Yichin Chen; Che-Ming Yang; En-Lun Zhang; Joanna Méndez; Chia-Han Tseng; Filip Hartvich; et al. (Engineering Geology, 2024)

From the fat body to the hemolymph: Profiling tick immune and storage proteins through transcriptomics and proteomics - Veronika Urbanová; Stephen Lu; Eliška Kalinová; Larissa Martins; Tereza Kozelková; Filip Dyčka; José M. Ribeiro; Ondřej Hajdušek; Jan Perner; Petr Kopáček (Insect Biochemistry and Molecular Biology, 2024)

Source area morphometry and high depletion rate of landslides may indicate their coseismic origin - Ivo Baroň; Jan Jelének; Jan Klimeš; Jia-Jyun Dong; Rostislav Melichar; Martin Šutjak; Yichin Chen; Che-Ming Yang; En-Lun Zhang; Joanna Méndez; Chia-Han Tseng; Filip Hartvich; et al. (Engineering Geology, 2024)

The effect of tree growth disturbances inertia on dendrogeomorphic spatio-temporal analysis of landslides: A case study - Karel Šilhán; Andrea Fabiánová; Jan Klimeš; Petr Tábořík; Filip Hartvich; Jan Blahůt (CATENA, 2024)

Measurement of dosimetrical cross sections with 14.05 MeV neutrons from compact neutron generator - Michal Kostal; Tomáš Czakoj; Petr Alexa; Jan Šimon; Marek Zmeškal; Martin Schulc; Alena Krechlerová; Tomáš Peltán; Filip Mravec; František Cvachovec; Vojtěch Rypar; Radim Uhlář; et al. (Annals of Nuclear Energy, 2023)

Radar-based measurements of the solids flow in a circulating fluidized bed - Diana Carolina Guío-Pérez; Marlene Bonmann; Tomas Bryllert; Martin Seemann; Jan Stake; Filip Johnsson; David Pallarès (Fuel, 2023)

Elemental profile identifies metallurgical pollution in epiphytic lichen Xanthoria parietina and (hypo)xanthine correlates with metals - Jozef Kováčik; Lenka Husáková; Mihaela Vlassa; Martina Piroutková; Marek Vydra; Jan Patočka; Miuța Filip (Science of The Total Environment, 2023)

Proglacial streams runoff dynamics in Devil´s Bay, Vega Island, Antarctica - Jan Kavan; Filip Hrbáček; Christopher D. Stringer (Hydrological Sciences Journal, 2023)

The Miocene Climatic Optimum at the interface of epicontinental sea and large continent: A case study from the Middle Miocene of the Eastern Paratethys - Yuliia V. Vernyhorova; Katarína Holcová; Nela Doláková; Bettina Reichenbacher; Filip Scheiner; Lukáš Ackerman; Jan Rejšek; Lorenzo De Bortoli; Jakub Trubač; Torsten Utescher (Marine Micropaleontology, 2023)

Anatomical growth response of Fagus sylvatica L. to landslide movements - Karel Šilhán; Jan Balek; Filip Hartvich; Jan Klimeš; Jan Blahůt; Filip Hampel (Science of The Total Environment, 2023)

A tapt1 knock-out zebrafish line with aberrant lens development and impaired vision models human early-onset cataract - Tamara Jarayseh; Brecht Guillemyn; Hanna De Saffel; Jan Willem Bek; Delfien Syx; Sofie Symoens; Yannick Gansemans; Filip Van Nieuwerburgh; Sujatha Jagadeesh; Jayarekha Raja; Fransiska Malfait; Paul J. Coucke; et al. (Human Genetics, 2023)

Evolution of palaeoclimate, palaeoenvironment and vegetation in Central Europe during the Miocene Climate Optimum - Filip Scheiner; Martina Havelcová; Katarína Holcová; Nela Doláková; Slavomír Nehyba; Lukáš Ackerman; Jakub Trubač; Šárka Hladilová; Jan Rejšek; Torsten Utescher (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Characterisation of neutron field in large graphite insertion in special core of the LR-0 reactor - Tomáš Peltan; Eva Vilímová; Tomáš Czakoj; Zdeněk Matěj; Filip Mravec; František Cvachovec; Jan Šimon; Vlastimil Juříček; Michal Košťál (Annals of Nuclear Energy, 2023)

Vehicle cabin air quality: influence of air recirculation on energy use, particles, and CO2 - Dixin Wei; Filip Nielsen; Hannes Karlsson; Lars Ekberg; Jan-Olof Dalenbäck (Environmental Science and Pollution Research, 2023)
In this study, simulations were performed to investigate the influence of different vehicle climate ventilation strategies, mainly the air recirculation (REC) degree, on the cabin air quality and climate system power. The focus of air quality is on the cabin particle concentrations including PM 2.5 (particles of aerodynamic diameter less than 2.5 μm), UFP (ultrafine particles of aerodynamic diameter less than 100 nm), and cabin CO 2 concentration. Three outside climates (cold, intermediate, and warm) and three outside particle concentrations are studied. The studied vehicle originally shows possibilities to meet WHO PM 2.5 guideline of 15 μg/m 3 with a new filter. The aged filter have reduced performance, especially when outside concentration is high. Increased REC shows advantages in all the three climates in reducing particles and climate power for the studied vehicle. Application of 70% REC (70% of ventilation air is recirculated air) on average lowers PM 2.5 by 55% and 39% for a new and aged filter, respectively. 70% REC with a new filter reduces cabin PM 2.5 below guideline of 15 μg/m 3 in all conditions. The reduction of UFP counts results are generally similar to that of PM 2.5 . Increased REC also lessens the average climate system power by up to 27% on average. When REC is increased, the cabin CO 2 concentration arises accordingly, and the magnitude is relevant to the passengers. In all studied conditions with 1 passenger, 70% REC does not increase CO 2 above the common guideline of 1000 ppm. 70% REC is not recommended with more than 1 passengers in cold and intermediate climate and 2 passengers in warm climate. Besides, to avoid the potential windscreen fog risk in cold climate, REC should be avoided when passengers are more than 3. Except for constant REC values, a sample study investigates a dynamic control of the REC. It shows the possibility of continuously optimizing REC to reduce the climate power and particles, while maintaining the CO 2 concentration below 1000 ppm. In warm climate with 1 passenger boarded, the average optimized REC is 90%, which in comparison with base case lead to 44% PM 2.5 reduction and 12% climate power reduction.

Iron nitride nanoparticles for rapid dechlorination of mixed chlorinated ethene contamination - Miroslav Brumovský; Vesna Micić; Jana Oborná; Jan Filip; Thilo Hofmann; Daniel Tunega (Journal of Hazardous Materials, 2023)

Changes of the aridity index in Europe from 1950 to 2019 - Zuzana Bešt́áková; Filip Strnad; Mijael Rodrigo Vargas Godoy; Ujjwal Singh; Yannis Markonis; Martin Hanel; Petr Máca; Jan Kyselý (Theoretical and Applied Climatology, 2023)

Macroinvertebrate assemblages in acidified mountain lake inflows differs from lake outflows: the influence of lakes - Kateřina Dočkalová; Takaaki Senoo; Daniel Vondrák; Pavel Chvojka; Jiří Kopáček; Lenka Kamasová; Filip Beneš; Jan Špaček; Jolana Tátosová; Peter Bitušík; Arne Fjellheim; Evžen Stuchlík (Biologia, 2022)

Consensus Paper: Strengths and Weaknesses of Animal Models of Spinocerebellar Ataxias and Their Clinical Implications - Jan Cendelin; Marija Cvetanovic; Mandi Gandelman; Hirokazu Hirai; Harry T. Orr; Stefan M. Pulst; Michael Strupp; Filip Tichanek; Jan Tuma; Mario Manto (The Cerebellum, 2022)

Size-resolved simulation of particulate matters and CO2 concentration in passenger vehicle cabins - Dixin Wei; Filip Nielsen; Lars Ekberg; Jan-Olof Dalenbäck (Environmental Science and Pollution Research, 2022)
The main aim of this study is to develop a mathematical size-dependent vehicle cabin model for particulate matter concentration including PM 2.5 (particles of aerodynamic diameter less than 2.5 μm) and UFPs (ultrafine particles of aerodynamic diameter less than 100 nm), as well as CO 2 concentration. The ventilation airflow rate and cabin volume parameters are defined from a previously developed vehicle model for climate system design. The model simulates different filter statuses, application of pre-ionization, different airflow rates and recirculation degrees. Both particle mass and count concentration within 10–2530 nm are simulated. Parameters in the model are defined from either available component test data (for example filter efficiencies) or assumptions from corresponding studies (for example particle infiltration and deposition rates). To validate the model, road measurements of particle and CO 2 concentrations outside two vehicles were used as model inputs. The simulated inside PM 2.5 , UFP and CO 2 concentration were compared with the inside measurements. Generally, the simulation agrees well with measured data (Person’s r 0.89–0.92), and the simulation of aged filter with ionization is showing higher deviation than others. The simulation using medium airflows agrees better than the simulation using other airflows, both lower and higher. The reason for this may be that the filter efficiency data used in the model were obtained at airflows close to the medium airflow. When all size bins are compared, the sizes of 100–300 nm were slightly overestimated. The results indicated that among others, expanded filter efficiency data as a function of filter ageing and airflow rate would possibly enhance the simulation accuracy. An initial application sample study on recirculation degrees presents the model’s possible application in developing advanced climate control strategies.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Transcription factor c-Myb: novel prognostic factor in osteosarcoma - Kamila Říhová; Monika Dúcka; Iva Staniczková Zambo; Ladislava Vymětalová; Martin Šrámek; Filip Trčka; Jan Verner; Stanislav Drápela; Radek Fedr; Tereza Suchánková; Barbora Pavlatovská; Eva Ondroušková; et al. (Clinical & Experimental Metastasis, 2022)

Analysis of the rainfall pattern triggering the Lemešná debris flow, Javorníky Range, the Czech Republic - Jana Smolíková; Filip Hrbáček; Jan Blahůt; Jan Klimeš; Vít Vilímek; Juan Carlos Loaiza Usuga (Natural Hazards, 2021)

The role of alanine glyoxylate transaminase-2 (agxt2) in β-alanine and carnosine metabolism of healthy mice and humans - Jan Stautemas; Natalia Jarzebska; Zhou Xiang Shan; Laura Blancquaert; Inge Everaert; Sarah de Jager; Siegrid De Baere; Arne Hautekiet; Anneke Volkaert; Filip B. D. Lefevere; Jens Martens-Lobenhoffer; Stefanie M. Bode-Böger; et al. (European Journal of Applied Physiology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

PM2.5 and ultrafine particles in passenger car cabins in Sweden and northern China—the influence of filter age and pre-ionization - Dixin Wei; Filip Nielsen; Lars Ekberg; Anders Löfvendahl; Maria Bernander; Jan-Olof Dalenbäck (Environmental Science and Pollution Research, 2020)
The main aim of the study was to evaluate the influence of filter status (new and aged), pre-ionization, on the particle filtration in modern passenger cars. Measurements of in-cabin and outside PM 2.5 (dp < 2.5 μm) concentration and UFP (ultrafine particle, dp < 100 nm) counts, to calculate I/O (indoor to outdoor) ratios, were performed. They were done at two locations, to study the influence of different outside conditions on the HVAC (heating, ventilation, and air-conditioning) system. The measurements were performed in two new cars, with similar HVAC systems and settings, using a new filter and an aged synthetic filter. Furthermore, an ionization unit was installed upstream of the filter in both cars. This enabled the study of filter status, with and without ionization, under common driving conditions. The results show that the HVAC system performances were very similar at the two locations, with average I/O ratios of 0.35–0.40 without ionization and 0.15–0.20 with ionization applied, although the outside conditions were considerably different. Furthermore, the aged filter clearly worsened the filtration ability. Considering the corresponding average PM 2.5 I/O ratios in one location as an example, the average for the new filter was 0.20 and 0.60 for the aged filter. The corresponding UFP I/O ratios were 0.24 and 0.57. Other findings are that the aged filter with ionization reached a performance close to the new filter (without ionization), and that increased ventilation airflow and decreased recirculation degree, as expected, led to an increase in the I/O ratio for both particle sizes.

Oxidative stress in microbes after exposure to iron nanoparticles: analysis of aldehydes as oxidative damage products of lipids and proteins - Jaroslav Semerád; Monika Moeder; Jan Filip; Martin Pivokonský; Alena Filipová; Tomáš Cajthaml (Environmental Science and Pollution Research, 2019)

Hospital wastewaters treatment: Fenton reaction vs. BDDE vs. ferrate(VI) - Tomáš Mackuľak; Roman Grabic; Viera Špalková; Noemi Belišová; Andrea Škulcová; Ondřej Slavík; Pavel Horký; Miroslav Gál; Jan Filip; Ján Híveš; Marian Vojs; Andrea Vojs Staňová; et al. (Environmental Science and Pollution Research, 2019)

Embryonic Cerebellar Graft Morphology Differs in Two Mouse Models of Cerebellar Degeneration - Zdenka Purkartova; Filip Tichanek; Yaroslav Kolinko; Jan Cendelin (The Cerebellum, 2019)

Climatic conditions and human activities shape diploid–tetraploid coexistence at different spatial scales in the common weed Tripleurospermum inodorum (Asteraceae) - Martin Čertner; Pavel Kúr; Filip Kolář; Jan Suda (Journal of Biogeography, 2019)
Aim While environmental conditions are reported as important determinants of cytotype distribution patterns in some mixed‐ploidy plant species, in others they seem to play no role. One reason for such inconsistency might be how and at what spatial scale the ecology of different cytotypes is compared. To address this issue, we adopted several complementary approaches to assess ecological requirements of cytotypes in a single species across wide‐range of spatial scales. Location Europe. Taxon Tripleurospermum inodorum (Asteraceae). Methods WorldClim extracted data were used for comparing climatic niches of T. inodorum diploids and tetraploids at continental and subcontinental scales and for predicting climatic suitability of habitats in Europe. Within the contact zone of cytotypes, at the regional scale, ecological preferences of cytotypes were assessed independently in three regions. Habitat types and ecological indicators inferred from species composition of vegetation in both uniform‐ploidy and mixed‐ploidy populations were used for ecological niche reconstructions. Results The two cytotypes differed in their climatic niches. However, due to considerable niche overlap, diploids and tetraploids were predicted to co‐occur in an extensive contact zone in Europe. Within the contact zone, cytotypes had identical ecological preferences but varied in their frequency at particular habitat types. The ecological niches of mixed‐ploidy and uniform‐ploidy populations were undistinguishable. Main conclusions Cytotype distribution patterns may be shaped by multiple environmental forces, each operating at a different spatial scale. In T. inodorum , climate is an important driver of cytotype distribution patterns at continental scale, however, at finer scales within the contact zone, the founder effect and non‐random migration patterns caused by human activities seem to be more important than environmental heterogeneity. The use of independent replicates and/or across‐scale comparisons can significantly improve the performance of ecological niche assessments.

Intracerebral EEG Artifact Identification Using Convolutional Neural Networks - Petr Nejedly; Jan Cimbalnik; Petr Klimes; Filip Plesinger; Josef Halamek; Vaclav Kremen; Ivo Viscor; Benjamin H. Brinkmann; Martin Pail; Milan Brazdil; Gregory Worrell; Pavel Jurak (Neuroinformatics, 2019)
Manual and semi-automatic identification of artifacts and unwanted physiological signals in large intracerebral electroencephalographic (iEEG) recordings is time consuming and inaccurate. To date, unsupervised methods to accurately detect iEEG artifacts are not available. This study introduces a novel machine-learning approach for detection of artifacts in iEEG signals in clinically controlled conditions using convolutional neural networks (CNN) and benchmarks the method’s performance against expert annotations. The method was trained and tested on data obtained from St Anne’s University Hospital (Brno, Czech Republic) and validated on data from Mayo Clinic (Rochester, Minnesota, U.S.A). We show that the proposed technique can be used as a generalized model for iEEG artifact detection. Moreover, a transfer learning process might be used for retraining of the generalized version to form a data-specific model. The generalized model can be efficiently retrained for use with different EEG acquisition systems and noise environments. The generalized and specialized model F1 scores on the testing dataset were 0.81 and 0.96, respectively. The CNN model provides faster, more objective, and more reproducible iEEG artifact detection compared to manual approaches.

Air temperature and lapse rate variation in the ice‐free and glaciated areas of northern James Ross Island, Antarctic Peninsula, during 2013–2016 - Klara Ambrozova; Kamil Laska; Filip Hrbacek; Jan Kavan; Jakub Ondruch (International Journal of Climatology, 2019)
Studies assessing air temperature variations and their dependence on altitude from the eastern side of the Antarctic Peninsula are sparse. In this paper, we analyse air temperature and near‐surface lapse rates from the Ulu Peninsula (James Ross Island, Antarctic Peninsula). The temperature data were acquired from nine sites both in ice‐free areas and glaciers of the Ulu Peninsula in 2013–2016. The most important factors influencing air temperature differences were sea‐ice conditions, topography and ground surface properties. During the study period, air temperature decreased with height with the mean lapse rate of 0.40 °C 100 m −1 for the ice‐free sites (10–375 m a.s.l.) and 0.43 °C 100 m −1 for the glaciated sites (268–539 m a.s.l.). However, the values were lower in winter (ice‐free: 0.02 °C 100 m −1 and glacier: 0.31 °C 100 m −1 ) than in summer (ice‐free: 0.62 °C 100 m −1 and glacier: 0.51 °C 100 m −1 ) for both categories. The air layer between 10 and 56 m a.s.l. in the ice‐free area revealed an almost year‐round air temperature inversion resulting in a mean lapse rate of −0.79 °C 100 m −1 and an air temperature inversion frequency reaching up to 43%. The temperature inversion frequency was 10% lower for the lowest air layer for the glacier category, which was between 268 and 356 m a.s.l. The land surface air temperature was the highest when the wind was from the northwest and lowest when it was from the south–southwest. The near‐surface lapse rate–wind direction relationship was the most pronounced for the air layer between 10 and 56 m a.s.l. with the lowest mean lapse rate for west–southwest wind (−2.83 °C 100 m −1 ) and the highest for east–northeast wind (0.41 °C 100 m −1 ).

The impact of wetland on neutral mine drainage from mining wastes at Luanshya in the Zambian Copperbelt in the framework of climate change - Ondra Sracek; Bohdan Kříbek; Martin Mihaljevič; Vojtěch Ettler; Aleš Vaněk; Vít Penížek; Jan Filip; František Veselovský; Imasiku Nyambe (Environmental Science and Pollution Research, 2018)

Long-Term Development of Embryonic Cerebellar Grafts in Two Strains of Lurcher Mice - Jan Cendelin; Zdenka Purkartova; Jakub Kubik; Erik Ulbricht; Filip Tichanek; Yaroslav Kolinko (The Cerebellum, 2018)

Silver ions increase plasma membrane permeability through modulation of intracellular calcium levels in tobacco BY-2 cells - Petr Klíma; Martina Laňková; Filip Vandenbussche; Dominique Van Der Straeten; Jan Petrášek (Plant Cell Reports, 2018)

Behind the scenes in urinalysis: to report or not to report - Samuel Azuz; Jan Berg Gertsen; Sofie Skovmand Rasmussen; Christian Salgaard Jensen; Erik Filip Jansåker; David Fuglsang-Damgaard (Infectious Diseases, 2017)

Zero-valent iron particles for PCB degradation and an evaluation of their effects on bacteria, plants, and soil organisms - Alena Ševců; Yehia S. El-Temsah; Jan Filip; Erik J. Joner; Kateřina Bobčíková; Miroslav Černík (Environmental Science and Pollution Research, 2017)

The pathogenesis, diagnosis, and management of metastatic tumors to the ovary: a comprehensive review - Ondřej Kubeček; Jan Laco; Jiří Špaček; Jiří Petera; Jindřich Kopecký; Alena Kubečková; Stanislav Filip (Clinical & Experimental Metastasis, 2017)

Antiretroviral treatment for HIV infection: Swedish recommendations 2016 - Jaran Eriksen; Jan Albert; Anders Blaxhult; Christina Carlander; Leo Flamholc; Magnus Gisslén; Filip Josephson; Olof Karlström; Lars Navér; Veronica Svedhem; Aylin Yilmaz; Anders Sönnerborg (Infectious Diseases, 2017)

Geochemical evidence for peat bog contribution to the streamflow generation process: case study of the Vltava River headwaters, Czech Republic - Jan Kocum; Filip Oulehle; Bohumír Janský; František Bůzek; Jakub Hruška; Lukáš Vlček (Hydrological Sciences Journal, 2016)

Do the rich get richer? Varying effects of tree species identity and diversity on the richness of understory taxa - Juliette Chamagne; C. E. Timothy Paine; Donald R. Schoolmaster; Robert Stejskal; Daniel Volarřík; Jan Šebesta; Filip Trnka; Tomáš Koutecký; Petr Švarc; Martin Svátek; Andy Hector; Radim Matula (Ecology, 2016)
Understory herbs and soil invertebrates play key roles in soil formation and nutrient cycling in forests. Studies suggest that diversity in the canopy and in the understory are positively associated, but these studies often confound the effects of tree species diversity with those of tree species identity and abiotic conditions. We combined extensive field sampling with structural equation modeling to evaluate the simultaneous effects of tree diversity on the species diversity of understory herbs, beetles, and earthworms. The diversity of earthworms and saproxylic beetles was directly and positively associated with tree diversity, presumably because species of both these taxa specialize on certain species of trees. Tree identity also strongly affected diversity in the understory, especially for herbs, likely as a result of interspecific differences in canopy light transmittance or litter decomposition rates. Our results suggest that changes in forest management will disproportionately affect certain understory taxa. For instance, changes in canopy diversity will affect the diversity of earthworms and saproxylic beetles more than changes in tree species composition, whereas the converse would be expected for understory herbs and detritivorous beetles. We conclude that the effects of tree diversity on understory taxa can vary from positive to negative and may affect biogeochemical cycling in temperate forests. Thus, maintaining high diversity in temperate forests can promote the diversity of multiple taxa in the understory.

PK/PD Modelling of the QT Interval: a Step Towards Defining the Translational Relationship Between In Vitro, Awake Beagle Dogs, and Humans - Eleonora Marostica; Karel Van Ammel; Ard Teisman; David Gallacher; Jan Van Bocxlaer; Filip De Ridder; Koen Boussery; An Vermeulen (The AAPS Journal, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

High expression of SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE coincides with initiation of various developmental pathways in in vitro culture of Trifolium nigrescens - Maria Pilarska; Przemysław Malec; Jan Salaj; Filip Bartnicki; Robert Konieczny (Protoplasma, 2016)

Modelling of drug-induced QT-interval prolongation: estimation approaches and translational opportunities - Eleonora Marostica; Karel Van Ammel; Ard Teisman; Koen Boussery; Jan Van Bocxlaer; Filip De Ridder; David Gallacher; An Vermeulen (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Physiologically Based Pharmacokinetic Predictions of Tramadol Exposure Throughout Pediatric Life: an Analysis of the Different Clearance Contributors with Emphasis on CYP2D6 Maturation - Huybrecht T’jollyn; Jan Snoeys; An Vermeulen; Robin Michelet; Filip Cuyckens; Geert Mannens; Achiel Van Peer; Pieter Annaert; Karel Allegaert; Jan Van Bocxlaer; Koen Boussery (The AAPS Journal, 2015)

The origin of unique diversity in deglaciated areas: traces of P leistocene processes in north‐ E uropean endemics from the Galium pusillum polyploid complex ( R ubiaceae) - Filip Kolář; Soňa Píšová; Eliška Záveská; Tomáš Fér; Martin Weiser; Friedrich Ehrendorfer; Jan Suda (Molecular Ecology, 2015)
The role of glacial oscillations in shaping plant diversity has been only rarely addressed in endemics of formerly glaciated areas. The Galium pusillum group represents a rare example of an ecologically diverse and ploidy‐variable species complex that exhibits substantial diversity in deglaciated northern Europe. Using AFLP and plastid and nuclear DNA sequences of 67 populations from northern, central, and western Europe with known ecological preferences, we elucidate the evolutionary history of lineages restricted to deglaciated areas and identify the eco‐geographic partitioning of their genetic variation. We reveal three distinct endemic northern lineages: (i) diploids from southern Sweden + the British Isles, (ii) tetraploids from southern Scandinavia and the British Isles that show signs of ancient hybridization between the first lineage and populations from unglaciated central Europe, and (iii) tetraploids from Iceland + central Norway. Available evidence supports a stepwise differentiation of these three lineages that started at least before the last glacial maximum by processes of genome duplication, interlineage hybridization and/or allopatric evolution in distinct periglacial refugia. We reject the hypothesis of more recent postglacial speciation. Ecological characteristics of the populations under study only partly reflect genetic variation and suggest broad niches of postglacial colonizers. Despite their largely allopatric modern distributions, the north‐European lineages of the G. pusillum group do not show signs of rapid postglacial divergence, in contrast to most other northern endemics. Our study suggests that plants inhabiting deglaciated areas outside the Arctic may exhibit very different evolutionary histories compared with their more thoroughly investigated high‐arctic counterparts.

Physiology-Based IVIVE Predictions of Tramadol from in Vitro Metabolism Data - Huybrecht T’jollyn; Jan Snoeys; Pieter Colin; Jan Van Bocxlaer; Pieter Annaert; Filip Cuyckens; An Vermeulen; Achiel Van Peer; Karel Allegaert; Geert Mannens; Koen Boussery (Pharmaceutical Research, 2015)

Large Late Pleistocene landslides from the marginal slope of the Flysch Carpathians - Tomáš Pánek; Filip Hartvich; Vlasta Jankovská; Jan Klimeš; Petr Tábořík; Miroslav Bubík; Veronika Smolková; Jan Hradecký (Landslides, 2014)

Serpentine ecotypic differentiation in a polyploid plant complex: shared tolerance to Mg and Ni stress among di- and tetraploid serpentine populations of Knautia arvensis (Dipsacaceae) - Filip Kolář; Markéta Dortová; Jan Lepš; Miloslav Pouzar; Anna Krejčová; Milan Štech (Plant and Soil, 2014)

Tracing an Intra-montane Fault: An Interdisciplinary Approach - Filip Hartvich; Jan Valenta (Surveys in Geophysics, 2013)

Analysis of ethanol in fermentation samples by a robust nanocomposite-based microbial biosensor - Jana Šefčovičová; Jaroslav Filip; Vladimír Mastihuba; Peter Gemeiner; Jan Tkac (Biotechnology Letters, 2012)

Thermal behavior of almandine at temperatures up to 1,200°C in hydrogen - Claudia Aparicio; Jan Filip; Henrik Skogby; Zdenek Marusak; Miroslav Mashlan; Radek Zboril (Physics and Chemistry of Minerals, 2012)

Glycerol-treated nuclear suspensions—an efficient preservation method for flow cytometric analysis of plant samples - Filip Kolář; Magdalena Lučanová; Jakub Těšitel; João Loureiro; Jan Suda (Chromosome Research, 2012)

Blue, complexly zoned, (Na,Mg,Fe,Li)-rich beryl from quartz-calcite veins in low-grade metamorphosed Fe-deposit Skály near Rýmařov, Czech Republic - Milan Novák; Petr Gadas; Jan Filip; Tomáš Vaculovič; Jan Přikryl; Bohuslav Fojt (Mineralogy and Petrology, 2011)

Attenuation of dissolved metals in neutral mine drainage in the Zambian Copperbelt - Ondra Sracek; Jan Filip; Martin Mihaljevič; Bohdan Kříbek; Vladimír Majer; František Veselovský (Environmental Monitoring and Assessment, 2011)

The majority of the genetic risk for Paget’s disease of bone is explained by genetic variants close to the CSF1, OPTN, TM7SF4, and TNFRSF11A genes - Pui Yan Jenny Chung; Greet Beyens; Steven Boonen; Socrates Papapoulos; Piet Geusens; Marcel Karperien; Filip Vanhoenacker; Leon Verbruggen; Erik Fransen; Jan Van Offel; Stefan Goemaere; Hans-Georg Zmierczak; et al. (Human Genetics, 2010)

The Pseudomonas aeruginosa patatin‐like protein PlpD is the archetype of a novel Type V secretion system - Richard Salacha; Filip Kovačić; Céline Brochier‐Armanet; Susanne Wilhelm; Jan Tommassen; Alain Filloux; Romé Voulhoux; Sophie Bleves (Environmental Microbiology, 2010)
Summary We discovered a novel secreted protein by Pseudomonas aeruginosa , PlpD, as a member of the bacterial lipolytic enzyme family of patatin‐like proteins (PLPs). PlpD is synthesized as a single molecule consisting of a secreted domain fused to a transporter domain. The N‐terminus of PlpD includes a classical signal peptide followed by the four PLP conserved blocks that account for its lipase activity. The C‐terminus consists of a POTRA (polypeptide transport‐associated) motif preceding a putative 16‐stranded β‐barrel similar to those of TpsB transporters of Type Vb secretion system. We showed that the C‐terminus remains inserted into the outer membrane while the patatin moiety is secreted. The association between a TpsB component and a passenger protein is a unique hybrid organization that we propose to classify as Type Vd. More than 200 PlpD orthologues exist among pathogenic and environmental bacteria, which suggests that bacteria secrete numerous PLPs using this newly defined mechanism.

The relation between treatment outcome and efavirenz, atazanavir or lopinavir exposure in the NORTHIV trial of treatment-naïve HIV-1 infected patients - Filip Josephson; Maria C. H. Andersson; Leo Flamholc; Magnus Gisslén; Lars Hagberg; Vidar Ormaasen; Anders Sönnerborg; Jan Vesterbacka; Ylva Böttiger (European Journal of Clinical Pharmacology, 2010)

Changes in GM1 ganglioside content and localization in cholestatic rat liver - Marie Jirkovská; Filip Majer; Jaroslava Šmídová; Jan Stříteský; Gouse Mohiddin Shaik; Petr Dráber; Libor Vítek; Zdeněk Mareček; František Šmíd (Glycoconjugate Journal, 2007)

Energy Content of Antarctic Mesopelagic Fishes: Implications for the Marine Food Web - Anton Van de Putte; Hauke Flores; Filip Volckaert; Jan Andries van Franeker (Polar Biology, 2006)

A Multiscale Network Model for Simulating Moisture Transfer Properties of Porous Media - Jan Carmeliet; Filip Descamps; Geert Houvenaghel (Transport in Porous Media, 1999)